A Comparison of the Direct Compression Characteristics of Andrographis paniculata, Eurycoma longifolia Jack, and Orthosiphon stamineus Extracts for Tablet Development - Yusof, Yus Aniza; Hamid, Aziana Azlin Abdul; Ahmad, So’bah; Razak, Norawanis Abdul; Ling, Chin Nyuk; Mohamed, Suhaila (IntechOpen, 2011)
None